The Mediating Roles of Emotional Regulation on Negative Emotion and Internet Addiction Among Chinese Adolescents From a Development Perspective - Liang, Lijuan; Zhu, Mingrui; Dai, Jiali; Li, Min; Zheng, Ya (Frontiers in Psychiatry, 2021)
Internet Addiction, the nine-item Patient Health Questionnaire (PHQ-9), the seven-item Generalized Anxiety (GAD-7) scale, the 14-item Perceived Stress Scale (PSS), and the Emotion Regulation Questionnaire (ERQ). Correlation analysis, structural equation modeling and multiple-group analysis were performed in SPSS Statistics version 23 (IBM, Armonk, NY) and AMOS version 21. The results showed that internet addiction was affected directly by depression and stress and indirectly by expressive suppression and cognitive reappraisal. Anxiety affected internet addiction through cognitive reappraisal, and stress affected internet addiction through expressive suppression. The emotional regulation strategies of expressive suppression and cognitive reappraisal have partial multilevel mediating effects on the link between depression, anxiety, and internet addiction, but expressive suppression played a complete mediating role in correlation with stress and internet addiction. Age equivalence was accepted, but gender equivalence was not established. The structural path from stress to expressive suppression revealed a significant gender difference, which reported critical ratios of differences (CRDs) was larger than 1.96(CRD = 2.749, p < 0.05). Thus, compared with girls, expressive suppression had a far greater negative influence on stress among boys.